1987
DOI: 10.1029/jc092ic04p03785
|View full text |Cite
|
Sign up to set email alerts
|

Ocean acoustic tomography: Mesoscale velocity

Abstract: The travel times of acoustic pulses transmitted in opposite directions over a 300‐km distance in mid‐ocean have been used to measure the fields of sound speed and absolute water velocity with mesoscale resolution. The experiment, which took place west of Bermuda during August and September 1983, consisted of transceivers on two moorings that sent and received signals every 2 hours for 21 days. Ray paths in opposite directions were found to be very nearly reciprocal; effects due to internal waves and mean curre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
1

Year Published

1989
1989
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 131 publications
(59 citation statements)
references
References 23 publications
0
58
1
Order By: Relevance
“…{2.6) Howe et al [1987] showed that internal waves and large scale velocity shears do not significantly perturb the reference ray path so that for a two-way transmission the ray paths are reciprocal to first order and for a one-way transmission the ray paths for the reference ray and the perturbed ray are identical. In the BSPF experiment, only the one-way transmission case is examined.…”
Section: Acoustic Tomographymentioning
confidence: 99%
See 1 more Smart Citation
“…{2.6) Howe et al [1987] showed that internal waves and large scale velocity shears do not significantly perturb the reference ray path so that for a two-way transmission the ray paths are reciprocal to first order and for a one-way transmission the ray paths for the reference ray and the perturbed ray are identical. In the BSPF experiment, only the one-way transmission case is examined.…”
Section: Acoustic Tomographymentioning
confidence: 99%
“…The formulation of the forward problem given here follows that of Howe et al [1987]. Using geometric optics, the travel time T; along a ray path f; in an ocean having a sound speed field C(x, t) and a current field u(x, t) is…”
Section: Acoustic Tomographymentioning
confidence: 99%
“…The idea was proposed by Munk and Wunsch (1979; as a practical tool for monitoring mesoscale fluctuations of an ocean basin. Several experiments have demonstrated the effectiveness of acoustic tomography in the mid ocean region (The Ocean Tomography Group, 1982;Cornuelle, 1983;Cornuelle et al, 1985;Howe et al, 1987). Until recently, it was not clear that tomography would be a viable approach in a shallow, range dependent region such as the Florida Straits.…”
Section: Historical Backgoundmentioning
confidence: 99%
“…The differential travel time for the ith ray, Ds i , may be related to the horizontal current velocity u(r,z) and reference sound speed C(z) in the ocean in the following form [Howe et al, 1987]:…”
Section: Formulationmentioning
confidence: 99%